THE DEVELOPMENT OF PARENTING INFORMATION SYSTEM FOR KINDERGARTEN BASED ON SMS-GATEWAY - Halimah Halimah; Anggi Andriyadi (STMIK Pringsewu Lampung, 2018)
Kinderganten is a second home for a children for about 5 – 7 years, it is accroded from national constitution No.20 year 2003 article 8 about early education for children. Based on it, kinderganten management should be able to coordinate with the parents in order to giving a centralized information to avoiding false information from unresponsible person. Delivering an Information to the parents is always be an issued whereas the parents is not available to be contacted by the management, for instance when the students go to the kinderganten for the half of day, the management could not contact the parents due to limited communication, therefore the students is going home alone. The teacher also have an issues to communicate with the parents regarding the development of their children, the development of sensor motoric, and the development of social life of their children. Given the background, it need a centered information system based on short message service (SMS)-gateway by using waterfall a method which using Life Cycle Development System. The system which will be develop will help a parents to gathering centered information from Kinderganten Management, therefore, if there is newest information regarding schedule of holiday, event, study, the parents will be informed soon and well.